Diorganotin Complexes of a Thiosemicarbazone, Synthesis: Properties, X-Ray Crystal Structure, and Antiproliferative Activity of Diorganotin Complexes. (20th June 2010) - Wiecek, Joanna; Kovala-Demertzi, Dimitra; Ciunik, Zbigniew; Zervou, Maria; Demertzis, Mavroudis A.
Abstract : The synthesis and spectral characterization of novel diorganotin complexes with 3-hydroxypyridine-2-carbaldehyde thiosemicarbazone, H 2 L (1), [SnMe 2 (L)] (2), [SnBu 2 (L)] (3), and [SnPh 2 (L)] (4) are reported. The single-crystal X-ray structure of complex [SnPh 2 (L)(DMSO)] (5) shows that the ligand is doubly deprotonated and is coordinated as tridentate ligand. The six coordination number is completed by two carbon atoms of phenyl groups. There are two similar monomers 5a (Sn1) and 5b (Sn51) in the asymmetric unit. The monomers 5a and 5b are linked through intermolecular hydrogen bonds of N–H–O and C–H–S type. C–H → π, intermolecular interactions, intra- and intermolecular hydrogen bonds stabilize this structure and leads to aggregation and a supramolecular assembly. The IR and NMR ( 1 H, 13 C and 119 Sn ) spectroscopic data of the complexes are reported. The in vitro cytotoxic activity has been evaluated against the cells of three human cancer cell lines: MCF-7 (human breast cancer cell line), T-24 (bladder cancer cell line), A-549 (nonsmall cell lung carcinoma) and a mouse L-929 (a fibroblast-like cell line cloned from strain L). Compounds 1, 3, and 4 were found active against all four cell lines. Selectivity was observed for complexes 3 and 4 which were found especially active against MCF-7 and T-24 cancer cell lines.